Institutional and Policy Assessment of Renewable Energy Sector in Afghanistan. (15th January 2017) - Ershad, Ahmad Murtaza
Abstract : Renewable energy resources could play a vital role in the sustainable economic, social, and environmental development of Afghanistan. Heavy reliance of rural households on firewood, rising costs of fossil fuels, outdoor and indoor air pollution, and climate change are some of the challenges that can be addressed by diversifying our power production fuel inputs and adopting renewable energy technologies. In order to deploy and scale up renewable energy technologies and improve access to sustainable energy, clear policies and targets and dedicated institutions are crucial. Fortunately, Afghan government with the support of international community is setting ambitious targets for the renewable energy sector and is encouraging national and international investors to take part in the generation, transmission, and distribution of renewable energy especially electricity through Power Purchase Agreements or very cheap land leases. Thus, the objectives of this report are (I) to review the existing institutions in the field of renewable energy, (II) to review renewable energy policies and targets in Afghanistan, and (III) to identify institutional and policy gaps and recommend solutions.